Multifunctional Materials from Aerobic Degradation of Epoxy Thermoset via Phosphotungstic Acid‐Involved Activation and Bonding. Issue 24 (8th November 2022) - Zhou, Xuelian; Zhang, Shun; An, Wenli; Zhao, Xu; Long, Yuwei; Liu, Xuehui; Xu, Shimei; Wang, Yu‐Zhong
Abstract: The growing scale of production of wind turbines represents a big challenge for chemical recycling of amine‐cured epoxy resin (EP) to achieve high‐efficiency degradation and high‐value utilization of degradation products. Here, H2 O2 /phosphotungstic acid (HPW) catalytic oxidation system is demonstrated to completely degrade EP thermoset with the solid recovery rate of 96% at a reaction temperature of 80 °C for 4 h. Owing to protonation and bonding effect of HPW to the amine groups, the degradation products had a weight‐average molecular weight of 4285 with narrow molecular weight distribution. They were used as dye adsorption blend films and supramolecular adhesives based on hydrogen bonding and coordination bonding respectively. The work demonstrates a feasible and promising method to recover the EP thermoset into high‐performance materials. Abstract : Controlled oxidative degradation of epoxy thermoset and utilization of the degradation products as multiple functional materials were achieved though activation and bonding effect of HPW.